ANALISIS PENGARUH KUALITAS PELAYANAN, KEPUASAN NASABAH, KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS NASABAH (Studi pada PT. Bank Rakyat Indonesia Tbk. Cabang Cilacap) - Zamroni, Zamroni (JURNAL EKONOMI, 2014)
The research was conducted on customers of PT. Bank Rakyat Indonesia Tbk. Cilacap branch with the title: "The Effect Analysis of Service Quality, Customer Satisfaction and Customer Loyalty belief systems (Study on PT Bank Rakyat Indonesia Tbk. Branch Cilacap). The purpose of this study was to determine the effect of service quality, customer satisfaction on trust, commitment and loyalty PT Bank Rakyat Indonesia Tbk Cilacap branch. The analytical tool used Structural Equation Modeling (SEM).From the research and analysis of the data it is concluded that: Quality of service and significant positive effect on customer satisfaction, the higher the quality of service higher customer satisfaction. Quality of service and significant positive effect on confidence, the higher the quality of service the higher customer confidence. Quality of service and significant positive effect on customer loyalty, the higher the quality of service higher customer loyalty. Customer satisfaction and a significant positive effect on confidence, the higher the higher the customer satisfaction customer confidence. Customer satisfaction and a significant positive impact on customer loyalty, higher customer satisfaction higher customer loyalty. Confidence positive and significant effect on customer loyalty, higher customer loyalty confidence higher. Customer satisfaction and a significant positive effect on commitment, the higher customer satisfaction the higher the customer commitments. Confidence positive and significant effect on the commitment, the higher customer. Commitment positive and significant effect on customer loyalty, higher customer loyalty. Confidence is able to mediate the effect of customer satisfaction on customer loyalty. Commitment is able to mediate the effect of customer satisfaction on customer loyalty.Based on the above conclusion, to increase customer loyalty, the quality of service should be improved by increasing the indicators: tangibles, reliability, responsiveness, assurance and empathy. And PT. Bank Rakyat Indonesia Tbk. Branch Cilacap boost confidence and commitment to improving customer satisfaction better.Â Keywords: Quality of Service, Customer Satisfaction, Trust, Commitment and Customer Loyalty